Problematika Kekayaan Sumber Daya Alam Kalimantan dalam Puisi Di Sini Karya Dahri Dahlan (Kajian Semantik-Semiotik) - Dwi Rijaya Hakiki; Helvika Desmilianti; Widyatmike Gede Mulawarman (Universitas Mulawarman, 2023)
This research focuses on the problematics of Kalimantan's natural resource wealth in the poem